Durasi Kerja dan Tingkat Kelelahan Karyawan Rumah Makan di Siantar Square, Pematangsiantar - Eka Saudur Sihombing; Riada Pasaribu; Meyana Marbun; Titin Wahyu (FORUM ILMIAH KESEHATAN, 2022)
Work duration that exceeds the provisions can cause work fatigue. The purpose of this study was to determine the relationship between work duration and the level of fatigue of restaurant employees in Siantar Square, Pematangsiantar. This study was a quantitative study using a cross-sectional design. The subjects of this study were 63 cafe employees who were selected by total sampling technique. Data were collected through filling out a questionnaire and then analyzed using the Kolmogorov-Smirnov test. The results showed that there was a relationship between work duration and the level of fatigue of restaurant employees in Siantar Square, Pematangsiantar in 2021, which was indicated by a p-value of 0.000. It was concluded that the duration of work is a factor that causes work fatigue for restaurant employees. It is hoped that the results of this study can be taken into consideration for restaurant employees so that they take advantage of their rest time as optimally as possible, as well as stretch their muscles in between work activities. Meanwhile, restaurant owners should pay more attention to the health conditions of their employees so that the quality of their work can also be optimized.Keywords: restaurant; employee; duration of work; work fatigue ABSTRAK Durasi kerja yang melebihi ketentuan dapat menyebabkan kelelahan kerja. Tujuan penelitian ini adalah untuk mengetahui hubungan antara durasi kerja dengan tingkat kelelahan karyawan rumah makan di Siantar Square, Pematangsiantar. Studi ini adalah penelitian kuantitatif dengan menggunakan rancangan cross-sectional. Subyek penelitian ini adalah 63 karyawan cafe yang dipilih dengan teknik total sampling. Data dikumpulkan melalui pengisian kuesioner lalu dianalisis menggunakan uji Kolmogorov-Smirnov. Hasil penelitian menunjukkan bahwa ada hubungan antara durasi kerja dengan tingkat kelelahan karyawan rumah makan di Siantar Square, Pematangsiantar pada tahun 2021, yang ditandai dengan p-value 0,000. Disimpulkan bahwa durasi kerja merupakan faktor yang menyebabkan kelelahan kerja karyawan rumah makan. Diharapkan hasil penelitian ini dapat menjadi bahan pertimbangan bagi karyawan rumah makan agar memanfaatkan waktu istirahat seoptimal mungkin, serta melakukan peregangan otot di sela-sela aktivitas kerja. Sementara bagi pemilik rumah makan agar lebih memperhatikan kondisi kesehatan para karyawan agar kualitas kerja para karyawan juga lebih dapat dioptimalkan.Kata kunci: rumah makan; karyawan; durasi kerja; kelelahan kerja